FOOT AND MOUTH DISEASE IN IRAQI NATIVE GAZELLE: VIRUS ISOLATION, SEROTYPING AND CHARACTERIZATION - S. AL-BANA, A.; O. SHONY, M. (The Iraqi Journal of Veterinary Medicine, 1988)
Foot and mouth disease (FMD) virus type 0 was isolated from blood of two dead gazelle (Gazella gazella) at the fenced gazelle garden, Baghdad, Iraq. Affected animals were showing errsions in the mouth cavity and foamy fluid tinged with blood oozing from the mouth, nostrils and anus. The virus was isolated in lamb testes (LT) cell culture and was identified and typed by applying complement fixation and virus and virus neutralization tests. The virus was able to agglutinate red blood cells of mice only and was resistant to lipid solvents. It was completly inactivated when exposed to 70°C and 60°C for 15 and 30 minutes respectively. Viral infectivity was abolished at PH 3-PH 5 and at PH 10-PH 11. The isolated virus was able to cause infection and death of baby mice after intracerebral and intraperitoneal inoculation. It was also able to cause FMD infection in sheep after intravenous inoculation